Numerical analysis and characterization of a Wankel pump as a miniaturized mixer. (14th July 2015) - Wan, Stephen; Huanming, Xia; Kumar, Pankaj
Abstract: In the present study, particle track simulations of inert particles belonging to two species (binary mixing), carried out using a commercially available CFD code indicate that pumps based on Wankel type geometries (Wankel pumps) are capable of functioning as mixers, as well as pumps; and hence such devices could also drive a semi-batch micro-reactor system. The numerical results reveal that mixing quality improves as the particles loop through the pump cavity and then saturates after a time, and that mixing rate increases with rotor speed. Examination of the structure of the flow-field suggests that the underlying mechanism of mixing is a combination of the stretching (resulting in particle dispersion) and folding of streamlines into Taylor-like vortex pairs, accounting for the vertical symmetry in the particle distributions. Differences in the flow structure, detected by plots of fluid velocity components, could account for differences in particle distributions generated for various rotor speeds.